PENGELOLAAN KEGIATAN PENGEMBANGAN SOFT SKILLS MELALUI PROGRAM MADRASAH DIGITAL DI LINGKUNGAN SEKOLAH - Galuh Prabowo; Ahmad Hadiq Syifa Al Fawaz; Nihayatul Wafiroh; Muhammad Fikri Algifari; Ziyad El Fayoumi (LP2M IAIN Sultan Amai Gorontalo, 2025)
Abstract The main objective of this study is to analyze the management of the Digital Madrasah program in improving students' soft skills. The program is targeted to develop students' communication, collaboration, problem-solving and leadership skills through a technology-based approach. The focus on this objective is grounded in the fact that in the digital era, soft skills play a key role in one's academic and professional success. This research used a qualitative approach with a case study method to analyze the management of the Digital Madrasah Program. Data were collected through observation, in-depth interviews with the madrasah principal, teachers, and students, and curriculum documentation. Descriptive analysis was used to describe the main elements of the program, including objectives, implementation, and outcomes. The findings are expected to provide insights into the effectiveness of digital-based soft skills development and practical recommendations for other madrasahs. The results of this study show meaningful outcomes in the development of students' soft skills, especially communication, teamwork, and problem-solving skills through technology. The program increased students' confidence in online communication and digital presentation, and strengthened collaboration through technology-based projects. The development of critical thinking skills is also encouraged through the utilization of digital tools to solve complex challenges. The findings are in line with constructivism and self-efficacy theories that emphasize learning through experience and social interaction. This research contributes to the literature of technology integration in education for 21st century skills. Keywords: Soft Skills, Digital Madrasah, school environment